Evolution of Microstructure and Properties of Steel 22MnB5 due to Short Austenitization with Subsequent Quenching. Issue 12 (4th May 2016) - Andreiev, Anatolii; Grydin, Olexandr; Schaper, Mirko
Abstract : In this work, the influence of rapid heat treatment with short low‐temperature austenitization at different soaking temperatures on strength properties of tool‐quenched low‐carbon steel is presented. Two different modes of heat treatment for 22MnB5 have been carried out: conventional austenitization for 300 s at 950 °C and short austenitization for 2 s at soaking temperatures from 830 to 900 °C with subsequent quenching in water‐cooled dies. Subsequently, the mechanical properties of the heat‐treated material have been analyzed by means of tensile testing and hardness measurements. Furthermore, the effect of the initial microstructure upon the mechanical properties and the resulting microstructure after short time austenitization have been studied. It has been shown that hardness, yield, and tensile strength are higher after all modes of rapid heat treatment with involving short time austenitization in comparison with conventional furnace heat treatments. Steels with an initial microstructure consisting of ferrite, bainite, as well as pearlite exhibit improved mechanical properties after short austenitization comparing to steels with an initial microstructure consisting of solely ferrite and pearlite. Abstract : Combination of rapid heating with press hardening for production of crash‐relevant elements of "body‐in‐white" promises significant reduction of heating duration and production area with improvement of mechanical properties of finished components. The steel 22MnB5 after rapid heating to austenitization temperature, soaking within 2 s, and subsequent quenching exhibits up to 10% increased strength properties and significantly reduced decarburized layer thickness in comparison with material processed by means of conventional technology.